Case report: Primary CDK4/6 inhibitor and endocrine therapy in locally advanced breast cancer and its effect on gut and intratumoral microbiota - Vilhais, Guilherme; Alpuim Costa, Diogo; Fontes-Sousa, Mário; Ribeiro, Pedro Casal; Martinho, Filipa; Botelho de Sousa, Carolina; Santos, Catarina Rodrigues; Negreiros, Ida; Canastra, Ana; Borralho, Paula; Guia Pereira, Ana; Marçal, Cristina; et al. (Frontiers in Oncology, 2024)
Locally advanced breast cancer poses significant challenges to the multidisciplinary team, in particular with hormone receptor (HR) positive, HER2-negative tumors that classically yield lower pathological complete responses with chemotherapy. The increasingly significant use of CDK 4/6 inhibitors (CDK4/6i) plus endocrine therapy (ET) in different breast cancer settings has led to clinical trials focusing on this strategy as a primary treatment, with promising results. The impact of the microbiota on cancer, and vice-versa, is an emerging topic in oncology. The authors report a clinical case of a postmenopausal female patient with an invasive breast carcinoma of the right breast, Luminal B-like, staged as cT4cN3M0 (IIIB). Since the lesion was considered primarily inoperable, the patient started letrozole and ribociclib. Following 6 months of systemic therapy, the clinical response was significant, and surgery with curative intent was performed. The final staging was ypT3ypN2aM0, R1, and the patient started adjuvant letrozole and radiotherapy. This case provides important insights on primary CDK4/6i plus ET in locally advanced unresectable HR+/HER2- breast cancer and its potential implications in disease management further ahead. The patient’s gut microbiota was analyzed throughout the disease course and therapeutic approach, evidencing a shift in gut microbial dominance from Firmicutes to Bacteroidetes and a loss of microbial diversity following 6 months of systemic therapy. The analysis of the intratumoral microbiota from the surgical specimen revealed high microbial dissimilarity between the residual tumor and respective margins.